Research Methods in the Geography of Pilgrimage - Sołjan, Izabela; Bilska-Wodecka, Elżbieta (Turyzm/Tourism, 2005)
The aim of the article is to discuss the main research methods used in the geography of pilgrimage through an analysis based on already existing works published both in Poland and outside. The following groups of research methods were identified: those based on primary sources, those which refer to handwritten sources and iconographic materials, those based on secondary sources and, finally, cartographic methods